Mandated severance pay and firing cost distortions: A critical review of the evidence - Donald O. Parsons (Institute for the Study of Labor (IZA), 2011)
Severance pay mandates are an appealing job displacement insurance strategy in developing countries, which have only modest government administrative capacities, but they carry the threat of adverse indirect effects. A critical review of the empirical literature reveals that severance benefit mandates, unaccompanied by other labor regulations, have little apparent impact on labor market behaviors. Indeed many severance mandates in the industrialized world do not greatly exceed those provided voluntarily in larger firms in the U.S. Benefit mandates in the developing world are sometimes more extravagant, and the absence of substantial effects may result from limited enforcement. Broader economic regulations do appear to have substantial, adverse effects on the labor market, but it is important not to equate these with simple severance insurance plans.
urn:nbn:de:101:1-20110621356
Keywords: J08; J65; J33; 330; severance pay; firing costs; hiring costs; separation rate; employment